PEMETAAN POTENSI PARIWISATA DALAM MENDUKUNG PENGEMBANGAN PARIWISATA DI DESA SERANGAN - I Made Darma Oka; I Nyoman Winia; I Ketut Sadia (P3M Politeknik Negeri Bali, 2018)
Serangan Village is one of the famous tourist destinations in the island of Bali both by domestic tourists and foreign tourists. The existence of this destination is very strategic because it is 10 km from Denpasar city. Serangan village is very potential to be developed into a tourism village because it has a unique tourist attraction to support the development of tourism, namely: natural tourist attraction (Pura Sakenan, Pura Dalem Cemara, marine tourism, turtle conservation, manggrove ecotourism); cultural tourism attraction (cultural custom, telek dance); and special tourist attractions (culinary, souvenirs craft shells). The tourist attraction above is a big capital in tourism development in the Serangan village. However, all potentials must be managed professionally so that tourism development in Serangan village can be sustainable. The goal is that tourist attractions in Serangan village can be enjoyed by the current generation and future generations. Therefore, its management must be involved all stakeholders both government, private sector, and the community as the owner of Serangan village.Therefore, it is suggested to all stakeholders to synergize in determining the direction of tourism development policy of Serangan tourism village so as to be able to compete competitively with other tourist villages in Bali. Keywords: Potency, tourism development, tourism village.